Peran Orang Tua dalam Menanggulangi Kecanduan Bermain Game Anak: Studi Kasus di Desa Jantuk Kabupaten Lombok Timur - Leila Asparini; Lalu Sumardi (AS-SABIQUN, 2023)
The purpose of this study is to provide an overview of how the role of parents is in providing efforts to control children’s habits of playing online games. The approach used is a qualitative approach. This type of research includes case studies. Sources of data from this study were obtained from informants, namely parents of children who like to play online games and community leaders in Jantuk Village. Data collection techniques were carried out by interviews and observation. The data analysis technique used is an interactive model developed by Miles, Huberman and Saldana which consists of three techniques, namely: data condensation, data display and drawing conclusions. The results showed that parental guidance in overcoming children who are addicted to online games has several ways, namely: limiting the use of gadgets to children, accompanying children to play, directing children to positive activities, giving advice, placing gadgets in a hidden place and setting a password on them. Gadgets, as well as giving consequences to children if they don’t comply with the rules made by parents. The results of assisting parents in dealing with children addicted to online games are that children are no longer addicted to online games, are more able to take advantage of time, are responsible when doing something and are more able to manage time when going to play and when doing their schoolwork, and will be more open to the environment. Surrounding.